Potassium Utilization in Cassava (Manihot utilissina Pohl) as Influenced by Neem Cake - Urea Blend - Manorama Thampatti K C (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1985)
Potassium utilization in cassava (manihot utilissima pohl.) as influenced by neem cake – urea blend. An investigation was carried out at the College of Horticulture, Vellanikkara, during the year 1983-84, which include a soil column study to understand the dynamics of NH4+- N and K+ ions when applied as urea or urea-neem cake blend either alone or along with muriate of potash. The columns were filled with soil collected from the field surface upto 60 cm depth. Each 15 cm was taken as a separate layer maintaining the same bulk density as observed in the field. Fertilizer treatments comprising, no fertilizer, urea or urea-neem cake blend to supply 100 ppm N and muriate of potash to supply 100 ppm K either alone or in combination were applied to the surface 15 cm soil and mixed thoroughly. The study indicated that under natural conditions NH4+ - N was concentrated more in the lower layers of soil beyond the root zone of cassava whereas potassium was concentrated more in the surface layers of 0-30 cm depth. Application of muriate of potash either alone or in combination with urea-neem cake blend increased potassium in the surface layer within eight hours after fertilizer application. When untreated urea granules were applied along with potassic fertilizer, a major part NH4+ - N was found either concentrated in lower layers, or nitrified and lost. But when urea-neem cake blend was applied along with potassic fertilizer a major part of nitrogen was retained as NH4+ - N in the surface layers upto two weeks and later it moved downwards. There was a drastic reduction of NH4+ - N status in the surface layers upto 45 cm after one week in untreated urea, whereas urea-neem cake blend maintained much of NH4+ - N in the surface 30 cm upto three weeks. Application of muriate of potash maintained highest potassium status followed by urea-neem cake blend along with muriate of potash. The maximum leaching loss of potassium was observed from untreated urea when applied along with muriate of potash. The loss was reduced considerably when potassic fertilizer was applied along with urea-neem cake blend. A field experiment was conducted as a continuation of the study carried out at the College of Agriculture, Vellayani, when urea-neem cake blend at 5:3 ratio increased nitrogen availability, nitrogen uptake and yield. But it had an adverse effect on potassium utilization of the crop resulting in poor quality tubers and the yield increase observed was not significant. The present experiment was planned to tide over this difficulty either by changing the time of application or increasing the rate of potassic fertilizer. Results of the experiment clearly showed that urea-neem cake blend increased nitrogen use efficiency of cassava as evident in higher soil available nitrogen and higher nitrogen uptake by the crop. When muriate of potash was applied one month after application of urea-neem cake blend, the uptake of potassium was not reduced considerably in the initial stages and at the same time uptake was comparatively higher at the sixth month and harvest stages. Potassium at 75 kg K2O ha-1 increased uptake of all nutrients and also produced maximum tuber yield of 21.39 tonnes ha-1, whereas application of potassium one month after application of urea-neem cake blend recorded 19.76 tonnes ha-1 of tuber yield which was on par with the former treatment. Potassium uptake at all major growth stages were significantly correlated with plant dry weight and tuber yield. Maximum benefit per rupee invested was obtained when the rate of potassium was raised from 50 kg K2O ha-1 to 75 kg K2O ha-1 along with 50 kg N as urea-neem cake blend. Changing the time of application of potassic fertilizers to one month and three months after planting also increased the benefit obtained. Both three treatments were on par with each other and significantly superior to others.